Climate-Related Variation in Body Dimensions within Four Lacertid Species - Volynchik, Stanislav (International Journal of Zoology, 2014)
A close relationship between habitat and external morphology is widespread among many animals, including reptiles. Here, I studied the relationship between abiotic environmental conditions and body size of four lacertid species (Phoenicolacerta laevis, Ophisops elegans, Acanthodactylus boskianus, and Mesalina guttulata) occurring in Israel. I examined the effect of average annual temperature and average annual precipitation on body and limb dimensions, using linear statistical models. Temperature- and precipitation-related geographic clines in body size showed the same trend among all species. Females displayed stronger phenotypic response to temperature gradient than conspecific males, suggesting a sex-specific effect of natural selection. Snout-vent length (SVL) was negatively correlated with temperature, supporting Bergmann’s rule in O. elegans and in female P. laevis and A. boskianus, but not in M. guttulata. Precipitation was positively related to SVL in O. elegans and M. guttulata, and in female P. laevis and A. boskianus. The relative extremity lengths, especially hind limb segments, generally increase towards hot and dry locations, following Allen’s rule. Among the Mediterranean region species (P. laevis, O. elegans) the morphological-environmental link with temperature was stronger than in desert dwellers (A. boskianus, M. guttulata), for which precipitation was the major determinant of spatial variation.